Resultados de encuestas ejecutadas y metodologia usada en la investigacion en campos de agricultores en el Valle de Yoro, Honduras - Amaya, I.A. (International Center for Tropical Agriculture, 1987)
During 1982, both the Research and Agricultural Extension National Programs in Honduras carried out joint and coordinated activities to integrate the farmer, the extensionist, and the reserarcher in the process of bean production. A survey was carried out to collect information on the climatic and edaphic characteristics of Valle de Yoro (Honduras), the agricultural and climatic problems, and the marketing of beans in the area as well as the research priorities. So far, an effective bait is being used for slug control, main pest of the crop. The steps for a new survey to be conducted in 1986 by the national program are presented. (CIAT)